2017
DOI: 10.3126/jssn.v17i2.17144
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of lidocaine and esmolol in attenuating the hemodynamic response to laryngoscopy and intubation

Abstract: Introduction: Transient hemodynamic instability is an inevitable outcome of laryngoscopy and intubation which can have serious effects in patients with COPD, heart disease and hypertension. Hemodynamic stability is one of the main goals of the anesthesiologist. This study was performed to compare the safety and effectiveness of lidocaine and esmolol in comparison to placebo-control group, in modifying the hemodynamic response to laryngoscopy and intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…17 Many studies have been done to prevent this rise in hemodynamic parameter using different stress blunting drugs. 18 Paracetamol, magnesium sulfate, and lignocaine are commonly available used drugs in operation room. These drugs have been used individually in attenuation of pressure response to laryngoscopy and intubation in intraoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…17 Many studies have been done to prevent this rise in hemodynamic parameter using different stress blunting drugs. 18 Paracetamol, magnesium sulfate, and lignocaine are commonly available used drugs in operation room. These drugs have been used individually in attenuation of pressure response to laryngoscopy and intubation in intraoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine at a dose of 0.5 mcg/kg as 10-min infusion was administered prior to induction of general anaesthesia attenuates the sympathetic response to laryngoscopy and intubation in patients undergoing myocardial revascularization. Koju RB et al; [11] observed that there was an increase in systolic blood pressure, diastolic blood pressure, heart rate were significantly lower (p<0.05) in esmol group when compared to lidocaine and placebo group but there was no statistical significance (P>0.05) between control and lidocaine group after laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 94%